Extended Producer Responsibility (EPR) in Malaysia – Towards a Sustainable Waste Management System - Kamaruddin, Hanim; Marwan, Muhamad Azham (The journal of contemporary issues in business and government, 2021)
Extended Producer Responsibility (EPR) is a widely used principle that focuses on the responsibility of manufacturers throughout the life-cycle of products taking into account their impacts on the environment for a sound sustainable waste management. The EPR has emerged as a significant tool conceptualized from the polluter pay principle (PPP) to regulate manufacturer’s role in controlling or preventing harmful consequences of their products into the environment. In this paper, the main discussion will revolve around the opportunities of establishing an EPR legal system in Malaysia especially in regards to supporting management of solid waste such as plastic. Existing Malaysian related waste management strategies are reviewed to seek opportunities in implementing EPR under the Circular Economy initiatives. The EPR implementation schemes in selected countries will also be highlighted in the context of sustainable waste management.